2021
DOI: 10.26663/cts.2021.0002
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of glasgow prognostic score in patients with non-small cell lung cancers undergoing pn2 pneumonectomy

Abstract: Background: The aim of this study was to assess the relationship between Glasgow Prognosis Score (GPS) and survival in patients who underwent pneumonectomy due to pN2 non-small cell lung cancer (NSCLC). Materials and Methods: A total of 45 patients who were determined to have pN2 disease after pneumonectomy between 2007 and 2016 were retrospectively analyzed. The patients were assigned a GPS between 0 and 2 as follows: elevated CRP level (>1.0 mg/dL) and hypoalbuminemia (<35 mg/dL) was classified as GPS 2, ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
1
0
1
Order By: Relevance
“…Kawashima et al reported that GPS was an independent prognostic factor in patients with operable lung cancer (25). Aker et al found that the GPS score was significant for survival in their study of patients undergoing pneumonectomy (26). According to the results of this study, the mortality of patients with postoperative GPS 2 was statistically significantly higher (p=0.03).…”
Section: Discussionsupporting
confidence: 46%
“…Kawashima et al reported that GPS was an independent prognostic factor in patients with operable lung cancer (25). Aker et al found that the GPS score was significant for survival in their study of patients undergoing pneumonectomy (26). According to the results of this study, the mortality of patients with postoperative GPS 2 was statistically significantly higher (p=0.03).…”
Section: Discussionsupporting
confidence: 46%
“…Despite advances in lung surgery, mortality and morbidity rates are still high [20][21][22]. The frequency of POC is affected by factors such as resection type, patient demographic characteristics, procedure duration, and intraoperative bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Bu nedenle çalışmamızda heterojeniteyi azaltmak için segmentektomi hastaları ile lobektomi hastaları aynı grupta değerlendirilmiştir. Pnömonektomi uygulanmasının mortalite ve morbiditeyi arttırdığı daha önce yapılan çalışmalarda bildirilmiştir fakat tümör evresi ileri olan hastalarda komplet rezeksiyon sağlamak amacı ile uygulanmaktadır (17)(18)(19)(20). Calarella ve ark.…”
Section: Discussionunclassified